Anti-hyperlipidemic effect of Hridayarnava Rasa - A randomized double blind clinical study - Chaudhari Swapnil; R Galib; B J Patgiri; P K Prajapati (Wolters Kluwer Medknow Publications, 2019)
Background: Hyperlipidemia is modifiable risk factor for cardiovascular diseases, and its prevalence is alarmingly increasing in India. Though different treatment modalities are effectively used in the conventional system, they have certain limitations including certain adverse effects. Ayurvedic metallic and herbo-mineral formulations are safely practiced in Indian subcontinent without any evident side effects. Hridayarnava Rasa is one such Ayurvedic herbo-metalo-mineral formulation containing Tamra Bhasma (incinerated copper) that is being successfully prescribed in the management of lipid disorders. Aims and Objectives: To evaluate antihyperlipidemic effect of two samples of Hridayarnava Rasa prepared by using Tamra Bhasma processed in Surana Kanda (HRTBS) and Panchamrita during Amritikarana (HRTBP). Materials and methods: Total 126 patients of hyperlipidemia fulfilling inclusion criteria were randomly grouped into two. Patients registered in one group (n = 62) were administered with 125 mg of HRTBP (Hridayarnava Rasa prepared by using Tamra Bhasma processed in Panchamrita for Amritikarana) and another Group (n =64) with HRTBS (Hridayarnava Rasa prepared by using Tamra Bhasma processed in Suranakanda for Amritikarana) twice daily for 8 weeks along with honey as an adjuvant in both groups. Results and Conclusion: Both the drugs have shown significant effect in reducing lipid parameters but the difference in between the groups is statistically insignificant. On comparison, HRTBP showed better results than HRTBS.